The effect of childhood obesity on respiratory function tests and airway hyperresponsiveness - Ulger, Zülal; Demir, Esen; Tanaç, Remziye; Gökşen, Damla; Gülen, Figen; Darcan, Sükran; Can, Demet; Coker, Mahmut (The Turkish Journal of Pediatrics, 2006)
The aims of this study were to investigate the effect of exogenous obesity on respiratory function tests, to define the relationship between the severity of obesity and respiratory function test parameters, and to detect the incidence of airway hyperresponsiveness and exercise-induced bronchospasm in an obese study group. This cross-sectional controlled study was done with 38 exogenous obese patients, aged 9 to 15 years, and 30 healthy children. Basal respiratory function test parameters were measured with spirometry. To display airway hyperresponsiveness, 4.5% hypertonic saline provocation test was used; exercise-induced bronchospasm incidence was defined with bicycle ergometry. Basal respiratory function test parameters were lower in the study group as compared with the control group. Exercise test was positive in 31.6% of the obese group and in 3.3% of the control group (P = 0.003). The provocation test with hypertonic saline test was positive in 18.4% of the obese group. There were strong negative correlations between body mass index (BMI), relative weight, skin fold thickness, waist/hip circumference ratio and basal forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and peak expiratory flow (PEF) values. The diagnosis and management of exercise-induced bronchospasm may improve exercise performance and physical activity, assist with weight loss, and break the vicious circle.